Acceptance of COVID-19 Vaccination during the COVID-19 Pandemic in Sei Penuh City - Hendra Dhermawan Sitanggang; Ummi Kalsum; Marta Butar Butar (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The incidence of COVID-19 has shown a downward trend in recent months, but transmission is still possible; it is because COVID-19 is still a pandemic, and there may be new variants that can cause an increase in cases. Countermeasures are carried out not only through prevention efforts by health protocols but also through vaccination efforts. Vaccines have proven to impact efforts to deal with the COVID-19 pandemic positively. Accepting the COVID-19 vaccine is one of the keys to fulfilling vaccination achievements. Sei Penuh City is one of the areas in Jambi Province where COVID-19 vaccination coverage is still low, at 53.6% as of August 28, 2022. Therefore, this study aimed to determine the determinants of COVID-19 vaccine acceptance in Sei Penuh City. A cross-sectional design study was applied and conducted in Sei Penuh City in July 2022. The population of this study were all people aged ≥18 years who live in Sei Penuh City, with a sample of 300 people. Sampling used a 2-stage cluster method using Probability Proportional to Size (PPS). Villages in this PPS are villages with COVID-19 vaccine coverage second dose less than 50%. Data were analyzed descriptively and analytically. The results showed that respondents who received a second dose or more of the vaccine were 54.7%. Multivariate analysis showed that health protocols (aPR=1.64; 95%CI: 0.99-2.70) and education level (aPR=1.38; 95%CI: 1.02-1.86) were associated with receiving a second dose of vaccines. This study found that health protocol was the most dominant risk factor for COVID-19 vaccine acceptance. Socialization and education still need to be carried out, especially about the urgency of the COVID-19 vaccine in facing the COVID-19 pandemic. In addition, people with low education levels need more attention in increasing the achievement of COVID-19 vaccination. Keywords: COVID-19 vaccine, education level, health protocol, preventive behaviour